Plate Tectonic Theory and Its Geological Implications - A Review of Some Recent Studies (International Journal of Scientific Research in Science and Technology, 2024)
The Plate Tectonic Theory is a cornerstone of modern geology, explaining the dynamic processes that shape the Earth’s surface through the movement of rigid lithospheric plates. This theory has led to profound insights into the formation of geological structures, earthquake distribution, volcanic activity, and the rock cycle. Recent advancements in technology, such as GPS, satellite imagery, and deep-sea exploration, have allowed scientists to refine the understanding of plate movements and interactions. This paper reviews recent studies that contribute to the ongoing evolution of the Plate Tectonic Theory, with a focus on new discoveries related to plate boundaries, seismic activity, and mantle dynamics. Notable studies have provided deeper insights into the mechanisms driving plate motion, the creation of mountain ranges through continental collisions, and the role of hotspots in volcanic activity. The geological implications of these findings include a better understanding of the Earth’s interior and its geodynamic processes. Despite significant progress, challenges remain in fully understanding the intricacies of plate movements, particularly at subduction zones and within the mantle. The paper concludes by highlighting future research directions and the importance of interdisciplinary approaches in advancing the field, emphasizing the need for further exploration to address unresolved questions in Earth sciences.